TANGGUNG JAWAB PEMILIK USAHA AYAM TERNAK TERHADAP PEMUKIMAN SETEMPAT BERDASARKAN PERSPEKTIF KUH PERDATA - nurbaiti, nurbaiti nur; Sari, Putri Kemala (Jurist Argumentum: Pemikiran Intelektual Hukum, 2024)
Chicken farming is a business that many people pursue. The existence of livestock chicken businesses located aroud residential areas definitely has a lot of impacts on the environment, both positive and negative impacts, such as the livestock chicken business in Geulima Jaya village which has an impact on the local community. Article 1368 of the civil code states that a person is not only responsible for losses caused by the actions of people, goods and animals that are his or her responsibility. The writing of this thesis aims to find out about the impact of the responsibilities of livestock chiken bisiness owners on local settlements based on the perspective of the civil code (research  in Geulima Jaya village) as well asefforts to resolve disputes that occur between the community and livestock chiken businees owners in Geulima Jaya village. This research use empirical juridical research methods and types and types of research in descriptive analysis, namely by conducting research using a qualitative approach with data collection techniques through field research and literature. The results of this research show that the impact of the responsibility of livestock business owners on local settlements based on the perspective of the Civil Code can be said that the owner of the livestock chicken business has taken several steps to reduce the impact of the business such as odors and flies, but the community still feels objections because it is considered that they are still not optimal in in terms of reducing waste odors and preventing existing flies. the resolving efforts are made by giving warnings/directions to business owners to maintain the cleanliness of the environment and as well as holding deliberations involving Geulima Jaya village officials, chicken business owners and the Geulima Jaya village community. However, these efforts have not completely resolved the existing disputes.